STUDI TENTANG MINAT MASUK DI PROGRAM STUDI D-3 KEBIDANAN KAMPUS TERPADU NGUDI WALUYO (STIE YPPI Rembang, 2014)
AbstractThis studyanalyzes the factorswhich influencethe join intention atStudies ProgramD-3 of Midwifery at NgudiWaluyo. Object ofthis studyis theIntegrated CampusNgudiWaluyo. Research problemrefers to thephenomenon ofstudentquantity decreasing ofD-3 obstetrics at NgudiWaluyo. The formulation ofthe problem in this studyare: how toincreasejoin intention of D-3 StudyPrograminIntegrated CampusMidwiferyNgudiWaluyo. The sample methodaims(purposive sampling) have beenrequiredtoobtainthe datain this study. The study used150respondentsandall respondentsarepublic and privatehigh school studentsin districts of Semarangaresittingin classXII. Data analysisusingStructural EquationModel(SEM) with acomputerprogramAmos18. Thisresearch modelmeetsthecriteriaGoodness ofFitchi square=(93 801); probability=(0.051); CMIN/DF=(1.285); RMSEA=(0.051); TLI=(0,960), and PNFI=(0.700).Results of this studyindicatethatsuchcommunicationsaffect thebrandimage ofword of mouth. Word of mouthandthe attractionon theoutput ofeducationservices effecting the join intention.Â Keywords : brand image, word of mouth, the appeal of educationalservicesoutput, join intention.Â